Thiamine-Binding Protein of Escherichia coli - Iwashima, Akio (1971)
The ability to transport thiamine in Escherichia coli was reduced by osmotic shock treatment with a concomitant release of a thiamine-binding protein; its formation was repressed by thiamine added to the growth medium.